2002
DOI: 10.1046/j.1365-2850.2002.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Trauma for all: a pilot study of the subjective experience of physical restraint for mental health inpatients and staff in the UK

Abstract: Violence and aggression is common in psychiatric inpatient units. Despite the near universal prevalence of restraint, there is very little published research on either the efficacy or the subjective effects of restraint on staff or patients. In this pilot study, semistructured interviews were given to the patients and staff involved in six untoward incidents in which the patient participant had been subject to manual physical restraint. Participants were interviewed as soon as possible after the occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
376
0
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 227 publications
(406 citation statements)
references
References 17 publications
10
376
0
14
Order By: Relevance
“…The results of the search indicated that in the last 14 years relevant studies equated to seven published papers. Of the seven studies identified; four were qualitative studies (Bonner et al 2002;Fish & Culshaw, 2005;Jones & Kroese, 2006;Perkins et al 2012), one study used mixed methods (Duxbury et al 2002), one study made use of a survey comprising of quantitative and qualitative questions (Lees et al 2003) and one was a quantitative study (Foster et al 2007). See Table 1 below for an overview of the studies.…”
Section: Search Strategymentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the search indicated that in the last 14 years relevant studies equated to seven published papers. Of the seven studies identified; four were qualitative studies (Bonner et al 2002;Fish & Culshaw, 2005;Jones & Kroese, 2006;Perkins et al 2012), one study used mixed methods (Duxbury et al 2002), one study made use of a survey comprising of quantitative and qualitative questions (Lees et al 2003) and one was a quantitative study (Foster et al 2007). See Table 1 below for an overview of the studies.…”
Section: Search Strategymentioning
confidence: 99%
“…Five of the studies (Duxbury 2002;Lees et al 2003;Fish & Culshaw, 2005;Foster et al 2007;Perkins et al 2012) gave voice specifically to mental health professionals regarding the use of restraint, while three (Bonner et al 2002;Duxbury 2002;Jones & Kroese, 2006 ) offered a voice to the service user.…”
Section: Overview Of the Research Strategiesmentioning
confidence: 99%
See 3 more Smart Citations